Influence of waste management infrastructure on source segregation of medical waste at a major referral hospital in Western Kenya - Otieno, Ojwang B.; Atieno, Jenniffer V.; Long’ora, Albert (European Scientific Journal, ESJ, 2025)
Medical wastes generated by healthcare facilities such as sharps, and chemical, pathological, infectious, and pharmaceutical wastes are hazardous and have been known to cause various infections such as Hepatitis B, Hepatitis C, and Human-Immune Virus (HIV). Various studies in MW have established that source segregation is an effective step in managing hospital waste and therefore, the most important step in reducing health hazards and environmental pollution. Hospitals are therefore required to put in place sufficient infrastructure such as personal protective equipment, storage as well as waste transportation equipment at strategic points within each department or floor. Jaramogi Oginga Odinga Teaching and Referral Hospital (JOOTRH) is a major facility in western Kenya generating approximately 68% of medical waste in Kisumu County. A recent public health study in western Kenya established that 72% of cleaners at JOOTRH were treated for sharps injuries while needle prick injuries accounted for 69% of wounds that occurred among waste recyclers in common dumping sites in Kisumu County. The purpose of this study was to establish the influence of waste management infrastructure on source segregation of medical waste at the JOOTRH. This was a descriptive survey that involved a sample size of 112 nursing officers, 41 doctors, 13 laboratory technicians, 20 clinical officers, and eight heads of departments. Semi-structured questionnaires and interview schedules were used to collect data from healthcare workers and heads of departments respectively. Findings showed that Hospital waste management infrastructure (β=.513) has a significant (p<0.05) influence on source segregation of medical waste, and contributes approximately 38.4% unit changes in source segregation of medical waste at JOOTRH (R2=.384). The study concludes that delays in procurement processes have led to instances of inadequacies in PPE and waste collection containers, causing cases of waste-related injuries. The study findings should inform policy formulation for effective source segregation of medical waste generated by healthcare facilities, thereby reducing associated injuries.